The versatile router [ - Umanoff, Craig; Warner, Pat , 1943- (A fine woodworking DVD workshop, 2004)
Pat Warner shows you how to rout clean circles and holes, how to make half-lapped joints at the ends of boards, and laps in the middle of boards that cross one another at any angle you choose. He covers the anatomy of a fixed-base router, the use of the collar guide, and how to get two different shapes from the same decorative-profile bit.